Impact of natural and/or chemical stressors on the freeze-tolerant and euryhaline enchytraeid, Enchytraeus albidus - Silva, Ana Luísa Patrício (2015)
Rapid climatic changes are taking place in Arctic, subarctic and cold temperate regions, where predictions point to an increase in freeze-thaw events, changes in precipitation, evaporation and salinity patterns. Climate change may therefore result in large impacts in ecosystem functioning and dynamics, especially in the presence of contaminants due to intense anthropogenic activities. Even though multiple stress approaches have received increasing interest in the last decades, the number of such studies is limited. In particular, knowledge on the effect of freezethaw events and salinity fluctuations on ecotoxicology of soil invertebrates is lacking, especially important when considering supralittoral species. Therefore, the aim of this thesis was to investigate the effects of low temperature and salinity fluctuations, singly and in combination with contaminants, in the freeze-tolerant and euryhaline enchytraeid Enchytraeus albidus. The assessment of population level endpoints (survival and reproduction), along with physiological and biochemical parameters such as levels of cryoprotectants, ice/water content, oxidative stress biomarkers, cellular energy allocation, and tissue concentration of chemicals (when applied), provided new and valuable knowledge on the effects of selected physical and chemical stressors in E. albidus, and allowed the understanding of adjustments in the primary response mechanisms that enable worms to maintain homeostasis and survival in harsh environments such as polar and temperate-cold regions. The presence of moderate levels of salinity significantly increased freeze-tolerance (mainly evaluated as survival, cryoprotection and ice fraction) and reproduction of E. albidus. Moreover, it contributed to the readjustments of cryoprotectant levels, restoration of antioxidant levels and changed singnificantly the effect and uptake of chemicals (copper cadmium, carbendazim and 4-nonylphenol). Temperature fluctuations (simulated as daily freeze-thaw cycles, between -2ºC and -4ºC) caused substancial negative effect on survival of worms previsouly exposed to non-lethal concentrations of 4-nonylphenol, as compared with constant freezing (-4ºC) and control temperature (2ºC). The decrease in cryoprotectants, increase in energy consumption and the highest concentration of 4-nonylphenol in the tissues have highlighted the high energy requirements and level of toxicity experienced by worms exposed to the combined effect of contaminants and freezing-thawing events. The findings reported on this thesis demonstrate that natural (physical) and chemical stressors, singly or in combination, may alter the dynamics of E. albidus, affecting not only their survival and reproduction (and consequent presence/distribution) but also their physiological and biochemical adaptations. These alterations may lead to severe consequences for the functioning of the ecosystems along the Arctic, subarctic and cold temperate regions, where they play an important role for decomposition of dead organic matter. This thesis provides a scientific basis for improving the setting of safety factors for natural soil ecosystems, and to underline the integration of similar investigations in ecotoxicology, and eventually in risk assessment of contaminants.